Unlocking the potential of Cascara with impact entrepreneurship: a journey from coffee by-product to market innovation - sourcing strategy - Engler, Daniel (2025)
This work project explores the innovative transformation of Cascara, a by-product of coffee production, into a functional, health-conscious beverage while laying the groundwork for an impactful and profitable business. Among global challenges in the coffee industry, such as economic vulnerability, social inequities, and environmental degradation, Cascara emerges as a promising solution. The project identifies opportunities for economic empowerment of small scale farmers, environmental conservation, and market innovation through Cascara's commercialization. The study follows a structured journey, addressing challenges and opportunities through diverse methodologies, ultimately identifying the sourcing strategy as a key focus area that got explored in depth. By adopting a circular value chain model, this work project aims to redefine the value chain, fostering sustainability and inspiring impact-driven entrepreneurship.